Line Riders prohibition, the Border Patrol, and the liquor war on the Rio Grande - Dolan, Samuel K. (Essex, Connecticut TwoDot, 2022)
"Spanning a nearly twenty-year period, from the end of World War I to repeal of the Eighteenth Amendment and beyond, The Line Riders reveals an often overlooked and violent chapter in American history and introduces the officers that guarded the international boundary when the West was still wild"--
Introduction: An imaginary line -- A veritable reign of crime -- Marked for death -- Lawlessness seems atmospheric -- Men of the highest type -- The smuggler's trail -- An eye for an eye -- Adios, Mama -- In mortal combat -- A gentleman of courage -- Tiro de Gracia -- Alto Federalies! -- Long chances -- Mortal fear -- Their ruthless warfare -- This deplorable situation -- Galvan's friends.
Includes bibliographical references and index.
113236
Keywords: Alcohol trafficking -- Mexican-American Border Region -- History; Prohibition -- Mexican-American Border Region -- History; Border patrols -- Mexican-American Border Region -- History; North America -- Mexican-American Border Region; History